Prognostic significance of bone morphogenetic protein 6 (BMP6) expression, clinical and pathological factors in clinically node-negative oral squamous cell carcinoma (OSCC). Issue 1 (January 2019) - Suton, Petar; Bolanca, Ante; Grgurevic, Lovorka; Erjavec, Igor; Nikles, Iva; Muller, Danko; Manojlovic, Spomenka; Vukicevic, Slobodan; Petrovecki, Mladen; Dokuzovic, Stjepan; Luksic, Ivica
Abstract: Bone morphogenetic protein 6 (BMP6) has unique properties regarding structure and function in supporting bone formation during development and adult life. Despite its known role in various malignant tumors, the prognostic significance of BMP6 expression in oral squamous cell carcinoma (OSCC) remains unknown. The aim of the study was to investigate immunohistochemical expression of BMP6 in OSCC in correlation with clinical and pathological parameters, disease recurrence and survival. In addition, we investigated other parameters in order to identify prognosticators of neck metastases and final outcome. The study included 120 patients with clinically T1-3N0 OSCC who were primarily surgically treated between 2003 and 2008. There were 99 (82.5%) male and 21 (17.5%) female patients. The five-year disease-specific survival for the whole cohort was 79.7%. Tumors smaller than 2 cm in diameter showed higher incidence of strong BMP6 expression. No statistical correlation was observed between other clinico-pathological factors and BMP6 expression. Expression of BMP6 was not associated with disease recurrence and survival. BMP6 may not serve as prognosticator of final outcome or recurrence in clinically node-negative OSCC subjects. In multivariate analysis predictors of poorer survival were positive surgical margin, moderate tumor cell differentiation and pathological involvement of levels IV and/or V.